Four Essays on International Entrepreneurship - Rättich, Gordian (Gabler, 2011)
Internationalization of business activities has become one of the main fields of interest in management research, influencing a broad range of academic areas such as strategic management, organizational science, operations management or economic institutions. In recent years the pace of internationalization has even increased. With his four essays on distinctive levels of International Entrepreneurship, Gordian Rättich provides an answer on some of the most essential challenges for entrepreneurial firms and shows how social groups, economic institutions and nations manage to overcome the challenges of internationalization and gain competitive advantage